DISAIN MODULAR RUMAH SUSUN (SUATU KAJIAN PENDAHULUAN SISTEM MODUL) - Diasana Putra, I Dewa Gede Agung (Jurnal Natah, 2012)
The rapid growth of population in urban area is not evidently followed by housing supply development. This condition causes the highly un-planed development of the density housing. By developing dwelling-flat is offering one of a good effort to solve this issue. This paper is a preliminary study of modular system design to provide the dwelling-flat for middle and low income people. This study merely concerns on design aspect of modular system and leaving out the discussion on culture and religion aspect. This paper is based on literature review from any resources The component of modular the dwelling-flat is developed by pre-cast system that consist of foundation, wall, column, beam, floor and roof. The system that is used to joint inter component is a wet joints system and the casting system is cast in situ.
Keywords: a house with several story, modular, cast in situ.